Diagnosis of a Stress Fracture Of a Metatarsal Bone with Point of Care Ultrasound (POCUS) - Alfred Doblinger (CINQUILL Medical Publishers Inc., 2024)
The early diagnosis of stress fractures is a challenge in daily primary care practice. Point of care ultrasound (POCUS) can be helpful in the diagnosis of early signs of an incipient stress fracture. A 52-year-old woman presented with a history of chronic overuse in the left forefoot. A sonographic examination in the area of the reported pain point on the third metatarsal (consistent with a marching fracture) showed a clear accumulation of fluid, corresponding to subperiosteal hematoma. After only two weeks of resting the forefoot, a repeat examination using POCUS showed clear callus formation. This confirmed the suspected diagnosis of an early stage stress fracture. This case shows a sensible and easy-to-learn way of using POCUS in general practice. POCUS in combination with clinical examination and anamnesis is a cost-effective and timely diagnostic option without radiation exposure.